Metformin enhances osteogenic differentiation of stem cells from human exfoliated deciduous teeth through AMPK pathway. (26th October 2020) - Zhao, Xuedan; Pathak, Janak L.; Huang, Wenyan; Zhu, Chuandong; Li, Yunyang; Guan, Hongbing; Zeng, Sujuan; Ge, Linhu; Shu, Yan
Abstract: Stem cells from human exfoliated deciduous teeth (SHEDs) are ideal seed cells in bone tissue engineering. As a first‐line antidiabetic drug, metformin has recently been found to promote bone formation. The purpose of this study was to investigate the effect of metformin on the osteogenic differentiation of SHEDs and its underlying mechanism. SHEDs were isolated from the dental pulp of deciduous teeth from healthy children aged 6 to 12, and their surface antigen markers of stem cells were detected by flow cytometry. The effect of metformin (10–200 μM) treatment on SHEDs cell viability, proliferation, and osteogenic differentiation was analyzed. The activation of adenosine 5′‐monophosphate‐activated protein kinase (AMPK) phosphorylation Thr172 (p‐AMPK) was determined by western blot assay. SHEDs were confirmed as mesenchymal stem cells (MSCs) on the basis of the expression of characteristic surface antigens. Metformin (10–200 μM) did not affect the viability and proliferation of SHEDs but significantly increased the expression of osteogenic genes, alkaline phosphatase activity, matrix mineralization, and p‐AMPK level expression in SHEDs. Compound C, a specific inhibitor of the AMPK pathway, abolished metformin‐induced osteogenic differentiation of SHEDs. Moreover, metformin treatment enhanced the expression of proangiogenic/osteogenic growth factors BMP2 and VEGF but reduced the osteoclastogenic factor RANKL/OPG expression in SHEDs. In conclusion, metformin could induce the osteogenic differentiation of SHEDs by activating the AMPK pathway and regulates the expression of proangiogenic/osteogenic growth factors and osteoclastogenic factors in SHEDs. Therefore, metformin‐pretreated SHEDs could be a potential source of seed cells during stem cell‐based bone tissue engineering.